A Hopeful Natural Product, Pristimerin, Induces Apoptosis, Cell Cycle Arrest, and Autophagy in Esophageal Cancer Cells. (14th May 2019) - Huang, Peng; Sun, Li-Ying; Zhang, Yan-Qiao
Abstract : Esophageal cancer is one of the most common malignant digestive diseases worldwide. Although many approaches have been established for the treatment of esophageal cancer, the survival outcome has not improved. Pristimerin is a quinone methide triterpenoid with anticancer, antiangiogenic, anti-inflammatory, and antiprotozoal activities. However, the role of pristimerin in cancers such as esophageal cancer is unclear. In this study, we investigated the role and mechanisms of action of pristimerin in esophageal cancer. First, we found that pristimerin can induce apoptosis in esophageal cancer in vivo and in vitro . CCK-8 and clonogenic assays showed that pristimerin decreased the growth of Eca109 cells. In addition, we found that pristimerin decreased the protein expression of CDK2, CDK4, cyclin E, and BCL-2 and increased the expression of CDKN1B. Meanwhile, pristimerin elevated the ratio of LC3-II/LC3-I. Otherwise, downregulation of CDKN1B can reduce the esophageal cancer tumor growth induced by pristimerin. In conclusion, our findings revealed an important role of pristimerin in esophageal cancer and suggest that pristimerin might be a potential therapeutic agent for this cancer.